2003
DOI: 10.1021/bi027310+
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome−Cytochrome c Interactions:  A Model System for Investigation of Proteasome Host−Guest Interactions

Abstract: Owing to its high thermal stability and structural simplicity, the archaebacterium Thermoplasma Acidophilum 20S proteasome was selected for mechanistic studies in this work. This oligomeric enzyme complex consists of a barrel-shaped 20S core (approximately 700kDa) comprised of four stacked seven-membered rings with a alpha(7)beta(7)beta(7)alpha(7) subunit structure situated around a 7-fold symmetry axis. The hollow interior of the proteasome has three large interconnected chambers with narrow (13 A diameter) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Specifically, it implies that in cases where substrate unfolding or translocation is not the rate-limiting step, as in this model system, storage must take place concurrently in both antechambers while the processive degradation is carried out within the catalytic chamber. Interestingly, accumulation of substrate does not appear to affect the proteolytic activity of the proteasome, because when a reversible inhibitor was employed Cyt c was digested as normal (25). It is possible therefore that the antechambers retain proteins in a partially folded state, allowing them to enter the catalytic chamber as soon as space allows (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it implies that in cases where substrate unfolding or translocation is not the rate-limiting step, as in this model system, storage must take place concurrently in both antechambers while the processive degradation is carried out within the catalytic chamber. Interestingly, accumulation of substrate does not appear to affect the proteolytic activity of the proteasome, because when a reversible inhibitor was employed Cyt c was digested as normal (25). It is possible therefore that the antechambers retain proteins in a partially folded state, allowing them to enter the catalytic chamber as soon as space allows (41).…”
Section: Discussionmentioning
confidence: 99%
“…Formation of the host-guest proteasome complex was monitored using their spectroscopic signatures, 409 nm (Cyt c) and 395 nm (GFP) as previously described (25). Briefly, 20S proteasomes (1 M) were inhibited with clasto-lactacystin-␤-lactone (70 M) for 30 min at 22°C prior to mixing with substrate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the GEMMA data, it appears that a distribution of myoglobin molecules is trapped by the inhibited proteasome. Although a previous study suggested that a single protein substrate, 12 kDa cytochrome c, can be sequestered intact in an inhibited proteasome complex, the heme group of cytochrome c was found to form a "knot" that could sterically hinder substrate processing [52]. Apomyoglobin, lacking the heme group, may be less sterically hindered from entering the 20S proteasome even from both ends of the complex.…”
Section: Esi-ion Mobility Of the 20 Proteasomementioning
confidence: 90%
“…As suggested by Dunn and coworkers [52], a potential protein substrate can be trapped within a proteasome core without proteolysis by using an irreversible proteasome inhibitor. Lactacystin binds specifically to Thr-1 of the ␤-subunit in a covalent manner to impart protease inhibition of the 20S proteasome.…”
Section: Esi-ion Mobility Of the 20 Proteasomementioning
confidence: 99%